Morning and evening prayer, the administration of the sacraments, and certain other rites and ceremonies of the Church of England [electronic resource] : together with hymns (Munsee and English) - Church of England.; Wampum, J. B. (John B.); Hogg, H. C. (London : Society for Promoting Christian Knowledge, 1886)
Text in Delaware (or Munsee) and English on opposite pages except for pages 165-171 which are entirely in Delaware (Munsee). Preface signed: John Wampum, or Chief Haw-bun-o. "This translation is not free from imperfections, but since it has been many years in use, and there are hindrances to its immediate revision, the Archbishop of Canterbury gives his imprimatur to this Edition for present use". "Pages 7-163 are an exact reprint, in slightly larger type, of pp. 1-157 of Rev. Mr. Flood's translation of the Morning and evening prayers, etc, 1847." --Bibliography of Algonquin languages / J. C. Pilling. "A few of these hymns have been translated by the Rev. Luckenbach, Moravian Missionary." --Pref., p. iii. Electronic reproduction. Mode of access: Internet. 44